Leucine-Rich Repeat Protein Family Regulates Stress Tolerance and Development in Plants - Hao Zhiqi; Wang Tingyi; Chen Dongdong; Shen Lan; Zhang Guangheng; Qian Qian; Zhu Li (Rice Science)
The leucine-rich repeat (LRR) protein family is involved in a variety of fundamental metabolic and signaling processes in plants, including growth and defense responses. LRR proteins can be divided into two categories: those containing LRR domains along with other structural elements, which are further subdivided into five groups, LRR receptor-like kinases, LRR receptor-like proteins, nucleotide-binding site LRR proteins, LRR-extensin proteins, and polygalacturonase-inhibiting proteins, and those containing only LRR domains. Functionally, various LRR proteins are primarily involved in plant development and responses to environmental stress. Notably, the LRR protein family plays a central role in signal transduction pathways related to stress adaptation. In this review, we classify and analyze the functions of LRR proteins in plants. While extensive research has been conducted on the roles of LRR proteins in disease resistance signaling, these proteins also play important roles in abiotic stress responses. This review highlights recent advances in understanding how LRR proteins mediate responses to biotic and abiotic stresses. Building upon these insights, further exploration of the roles of LRR proteins in abiotic stress resistance may aid efforts to develop rice varieties with enhanced stress and disease tolerance.